2009
DOI: 10.1111/j.1744-7917.2009.00256.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to elevated levels of manganese and nickel is not harmful to a cosmopolitan detritivore, Megaselia scalaris (Diptera: Phoridae)

Abstract: Environmental contamination with metals such as manganese (Mn) and nickel (Ni) often results in elevated concentrations of these metals in plant tissues. At high concentrations, these metals are known to have detrimental effects on certain insect herbivores. Using laboratory bioassays and artificial diet, we investigated the development and survival of a cosmopolitan insect detritivore, Megaselia scalaris (Diptera: Phoridae), exposed to concentrations of Mn and Ni reaching 2600 mg Mn/kg and 5200 mg Ni/kg dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…In agreement, it has been reported that Phoridae [37], collembolans [38], and Linyphiidae [39] are able to develop and survive in metal polluted sites, suggesting that these taxa are less sensitive to the high concentrations of metals, low pH, and altitude conditions encompassed by the present study. Although the drying of the naturally polluted site during the dry season could represent a confounding factor, the CCA indicated that the effect of metal pollution superseded any potential impacts related to this event.…”
Section: Discussionsupporting
confidence: 78%
“…In agreement, it has been reported that Phoridae [37], collembolans [38], and Linyphiidae [39] are able to develop and survive in metal polluted sites, suggesting that these taxa are less sensitive to the high concentrations of metals, low pH, and altitude conditions encompassed by the present study. Although the drying of the naturally polluted site during the dry season could represent a confounding factor, the CCA indicated that the effect of metal pollution superseded any potential impacts related to this event.…”
Section: Discussionsupporting
confidence: 78%
“…Megaselia scalaris , a common detritivore, has been known to develop on substances as diverse as human wounds and corpses 51 , 52 , modeling clay, and emulsion paint 53 , 54 . Their ability to grow and mature on these diets, with minimal effect on their survival, and their tolerance to heavy metals 42 makes any effect of pharmaceuticals at very low doses found in reclaimed water even more surprising. In our study, the females had no preference for untreated diets versus any treated diets.…”
Section: Discussionmentioning
confidence: 99%
“…This species will generally feed on a variety of decomposing plant and animal tissues, and acts as a vector of pathogens 39 , 41 . These insects are both fecund and hardy because females can lay over 650 eggs in 16 days and are tolerant of heavy metals 42 , 43 . The white, roughly football-shaped eggs, hatch after approximately 24 hours into white translucent larvae.…”
Section: Introductionmentioning
confidence: 99%
“…With imagoes the content of manganese decreased to 0.5% of the consumption even under maximum concentrations. Sorensen et al (2009) studied the survival rate of a cosmopolitan insect Megaselia scalaris (Loew, 1866), exposed to a Mn concentration of 2,600 mg kg -1 of dry mass. The insects with a diet Mn 260-2,600 mg kg -1 showed a significant decrease in the duration of their larval development, total duration of imago formation and breeding.…”
Section: Discussionmentioning
confidence: 99%